Candlestick charts : an introduction to using candlestick charts - Lambert, Clive (Harriman House, 2009)
Candlesticks are a fantastic way of getting a clear idea of market direction, and any changes that may be taking place in price trends. In this exciting new book, Clive Lambert walks you through what candlesticks are, the major patterns and importantly, the psychology behind them, using straightforward language that will appeal to all levels of ability.